Long-Term Gastrocolocutaneous Fistula after Endoscopic Gastrostomy: How Concerned Should We Be - Nunes,Gonçalo (2019)
Percutaneous endoscopic gastrostomy (PEG) is a safe technique for long-term enteral feeding. The most common PEGassociated adverse events are minor. Gastrocolocutaneous fistula (GCCF) results from misplacement of the PEG tube through the colon. The importance of this complication is not currently defined, and there is no clearly established therapeutic algorithm. The authors report a series of 3 cases of GCCF diagnosed and treated in a tertiary center. Case 1: An 88-year-old man underwent PEG due to head and neck cancer. The procedure was uneventful, and the patient remained asymptomatic. After the first PEG tube substitution performed at 6 months, stool drainage through the stoma was observed. Computed tomography (CT) showed a GCCF. After tube removal, the fistula spontaneously closed, and the patient remained under nasogastric feeding until death. Case 2: A 31-year-old man with hereditary spastic paraplegia was submitted to PEG without early complications. The patient remained asymptomatic, and 7 months later, replacement of the PEG tube was planned. Under endoscopic control, the primary tube was removed, but the balloon replacement tube, introduced through the skin, was not observed in the gastric lumen. CT displayed a GCCF that spontaneously closed after a few days. A combined laparoscopic and endoscopic approach was used to resect the fistula tracts and perform a new gastrostomy. Case 3: A 45-year-old man with cerebral palsy was referred to PEG. Skin transillumination was only observed transiently, and the abdominal puncture was performed obliquely. The patient remained asymptomatic until the 7th month, when the primary PEG tube replacement was performed. The percutaneously placed substitution tube did not reach the stomach. GCCF was evident on CT. The fistula spontaneously closed, and the patient was referred to elective surgery for laparoscopic gastrostomy. GCCF is an uncommon complication of PEG. Its clinical course seems to be benign with patients remaining asymptomatic under ambulatory enteral feeding for long periods until PEG tube replacement. Spontaneous fistula closure is the rule in this setting. Laparoscopic gastrostomy should be considered when a new PEG is advised and cannot be safely performed due to colon interposition.